AB0823 Scleroderma and silica: Erasmus syndrome in west north spain. (23rd January 2014) - Freire, M.; Alonso, M.; Alvarez, E.; Gonzalez, L.; Rivera, A.; Sopeña, B.
Abstract : Background: Progressive systemic sclerosis (PSS) is a complex multisystem connective tissue disease whith unknown aetiology, but environmental and genetic factors may play a role. Since the first association of silica exposure and PSS by Erasmus in 1957 [1], several case reports documented this co-existence [2], but with conflicting results depending on the population studied [3]. Objectives: To stablish the incidence and to describe the clinical and analytical characteristics of patients with Erasmus syndrome in our health area. Methods: Medical records of patients admitted to the Complejo Hospitalario Universitario of Vigo from 1994 to 2011 with the diagnosis of PSS were reviewed, selecting those with documented exposure to silica. Results: During this time, the diagnosis of PSS was confirmed in 86 inpatients. 10 patients (7 of the 13 total males, 3 of the 73 total females) had also documented environmental exposure to silica dust and were selected for the study. 6 patients had worked in granite quarries, one digging tunnels and the other 3 in ceramic factories. The mean age at diagnosis of scleroderma was 51 years (range 26-76). According the classification proposed by LeRoy and Medsger [4] six were diffuse and three limited variants. Other two were diagnosed of mixed connective tissue disease. The initial symptom was Raynaud's phenomenon (RP) in 50% and cutaneous sclerosis in 20%, having appeared a median of 1 year prior to diagnosis. Clinical manifestations at the moment of diagnosis were: dyspnoea 90%, RP 80%, esophageal dysmotility 70%, skin ulcers 40%, telangiectasia 30%, arthritis 30%, tendinopathy 20%, calcinosis and renal crisis 10%. Autoantibody positivity was observed as follows: 10 ANA (1 anticentromere pattern), 2 anti-dsDNA, 1 anti-SM, 1 anti-RNP, 6 anti-Scl70, 2 ACLA, 3 RF. In 9 patients we observed interstitial lung disease data on imaging tests. Impairment in the diffusion test was observed in 7 of the 8 patients in whom lung function studies were performed, 5 of them with also a typical restrictive ventilatory pattern and decreased forced vital capacity. Bronchoscopy and transbronchial biopsy was done in 4 patients, and fibrosis and deposition of silica was described in all samples. Transthoracic echocardiography was performed in 7 patients and estimated PASP was above 25 mmHg in 5. Right cardiac catheterization was performed only in 2 patients, with mPAP measure confirmatory of PAH. 7 patients died during follow-up, with a mean of 4.2 years from diagnosis. Cause of death was respiratory failure in 3 cases, refractory heart failure in 2, liver cirrhosis in one and unknown in another one. Conclusions: Erasmus syndrome is a common condition among men with PSS who require admission in our health area, diffuse variant being predominant. Clinical course of our patients is rapidly progressive, with frequent development of cardiopulmonary mixed complications and a median survival of 4.2 years from diagnosis. References: Erasmus LD. Scleroderma in goldminers of the Witwatersrand with particular reference to pulmonary manifestations. South African Laboratory and Clinical Medicine. 1957; 3:209-231. Ajlani H et al. Erasmus syndrome: case report. Rev Pneumol Clin 2009; 65:16-22. Zaghi G et al. Autoantibodies in silicosis patients and silica-exposed individuals. Rheumatol Int 2010; 30:1071-1075. LeRoy BC, Medsger TA Jr. Criteria for the Classification of Early Systemic Sclerosis. J Rheumatol. 2001; 28: 1573-1576 Disclosure of Interest: None Declared